Formative evaluation of an educational mobile application: An interactive myqiraat application - Ishak S.F.; Bahrin M.A.M.; Roni N.H.A.; Zulkifly Mohd Zaki; Khairul Anuar Mohamad; M. Norazizi Sham Mohd Sayuti; Muhammad Arif Musa (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA